AN ANALYSIS FACTORS WHICH AFFECT THE ACCURACY TIME OF REPORTING FINANCIAL COMPANIES BANKING AT STOCK EXCHANGE PERIOD 2018-2021 - Valentina br Tarigan; Lailan Sufinah; Mirnawati Buulolo; Ribka Sari Butar-Butar (SEAN Institute, 2023)
Research is done with the purpose of several factors that influence the speed with which a banking institution is recorded on the Indonesia Stock Exchange in informing its financial data, in the 2018-2021 period 1. This research uses quantitative description. Profitability, leverage, and liquidity are used as the testing factors and are accompanied by time which is used as the dependent variable. 48 banking companies are acting as the population in this study which has also been recorded on the IDX 2018-2021. Use approach purposive sampling in the process of determining the sample, which has 32 banks, with the results of 128 observations. There are 32 banking companies in the sample that meet the criteria and were tested during the 2018-2021 period. This study utilizes secondary data. The IDX official website is used as a documentation method for data collection methods, namely www.idx.co.id during the 2018-2021 period, timely reporting of banking institutions that have been recorded on the IDX has no significant effect on the profitability, liquidity, or leverage of these institutions.